Analisis SWOT pada Usaha Jeanette Thrift Maumere - Emilianus Eo Kutu Goo; Maria Fraisceis Canserina Anggun Parera; Angela Felisitas Ina Ritan; Yosefa Yuliatrix; Anamaria Ellyria D’Nisa; Sakarias Leanaldi; Vinsensius Alfarodino Keytimu (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purchase of secondhand goods, known as thrifting, involves acquiring and reselling pre-owned clothing at low cost. Originating from Western practices during the Great Depression in the United States, this activity is no longer solely about financial considerations it is also an effort to protect the ecosystem by reducing fashion waste and addressing the adverse impacts of fast fashion, such as pollution and unethical labor practices. In Indonesia, thrifting has expanded rapidly since the 2010s, supported by the creative industry, online access, and platforms like Shopee and Tokopedia. It contributes 10% to the nation’s creative economy (BPS 2022), with export value reaching Rp 100 trillion. This phenomenon has gained traction among young generations such as millennials and Gen Z, often aligning with local cultural traditions. In Maumere, a small city in East Nusa Tenggara with limited access to international fashion, thrifting has emerged as a primary option for students. Stores offer t-shirts, blouses, and dresses priced between Rp 20,000 and Rp 50,000, which suits their modest financial circumstances. Jeanette’s (Aunt Cindy’s) business focuses on top garments like crop t-shirts and crop blouses, leveraging online marketing through TikTok, Instagram, and Facebook to compensate for the store’s less-than-ideal location. This study employs a qualitative approach with direct interviews with Jeanette, using SWOT analysis for evaluation. Strengths: Affordable pricing and alignment with current fashion trends enhance customer loyalty. Weaknesses: Delayed inventory arrivals,